Game theoretic application for energy efficient mobility handling in wireless sensor network. Issue 9 (12th August 2020) - Maheshwari, Prachi; Sharma, Ajay K.; Verma, Karan
Abstract: Wireless sensor network (WSN) are used to sense, process, and send important information relating to surrounding environment. In these network, one of the important issue is timely delivery of packets to destination and thus avoiding packet loss when sensor nodes are mobile. Most of the current research does not allow handling of packets of mobile sensor nodes till next Time‐division multiple access (TDMA) schedule. In this work, we investigate the problem of allocating reserved slots to mobile nodes which come in vicinity of new cluster head in currenTDMAschedule only. We model allocation of reserved slots to mobile nodes as cooperative game. We then propose cooperative coordination scheme to allow cooperation among mobile sensor nodes for accessing of reserved slots with the objective of avoiding unnecessary delay and packet loss in the network. We consider solution for both the cases when reserved slot is limited to 1 and when reserved slots are more than 1. We then propose evolutionary game theory‐based slot allocation scheme for calculation of probability by solving nash equilibrium point. This probability is used by mobile nodes to send data packets to new cluster head. Our scheme avoids end to end delay of packets and network congestion due to buffer overflows. We then present extensive simulation results comparing our scheme with existing techniques. The results show higher performance in terms of average residual energy, network lifetime and packet delivery ratio etc. Abstract : 1. Cooperative Coordination scheme (CCS) is used to provide reserved TDMA slots to occasional mobile nodes to allow them to send data packets in current TDMA schedule. 2. Calculation of probability p used by occasional mobile nodes to send data packets to avoid congestion and packet loss in network is done. 3. This scheme can achieve efficient delivery of packets and avoid discarded messages due to buffer overflows.